PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA KELAS TINGGI SD - Dini Aulia; Naila Anjani; Nuru Azkia; Nayla Andella Septiani; Selvi Sri Kartika; Zahra Salsabila; Najwa Atsila Meilani; Siti Rahayu; Nia Rahmadhani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of contextual learning on the mathematics learning motivation of upper-grade elementary school students. Contextual learning is an approach that connects learning materials with daily life so that students can more easily understand the concepts being taught. This study used a quantitative approach with an experimental method. Data collection techniques were carried out through observation, questionnaires, and documentation. The results showed that the implementation of contextual learning was able to increase students’ motivation in learning mathematics, indicated by increased activeness, interest, and enthusiasm in participating in the learning process. In addition, students found it easier to understand the material because learning was related to real-life experiences. Therefore, contextual learning can be an effective alternative learning approach to improve the mathematics learning motivation of upper-grade elementary school students.